Quality assurance dimensions for e-learning institutions in Gulf countries. Issue 4 (23rd July 2020) - Anwar, Syed Aziz; Sohail, M. Sadiq; Al Reyaysa, Meera
Abstract : Purpose: It has been argued in the literature that quality assurance is a relative concept. In view of the new challenges (and opportunities) created by e-learning institutions in the Gulf Cooperation Council (GCC) countries, this paper aims to explore the dimensions of quality assurance in e-learning and test the psychometric properties of the underlying dimensions. Design/methodology/approach: A sequential mixed methods approach was applied in this study. In the qualitative phase, items were generated using the inductive and deductive approaches. This was then followed by the quantitative phase where data was collected from 275 senior academics, scholars and administrators associated with e-learning institutions in Kuwait, UAE and Saudi Arabia. Findings: The findings of this study revealed that e-learning quality assurance is a multidimensional construct. The dimensions of accreditation, assessment, accountability and benchmarking were identified. Further, the model demonstrated adequacy in its validity and reliability. Practical implications: In the light of proliferation of e-learning courses in GCC countries, the results of this are invaluable to enable administrators and instructors to design strategy and foster innovation in the domain of quality assurance. E-learning institutions operating in a competitive environment have to design and implement an effective strategy to achieve innovation, uniqueness and diversity in the educational sector of their countries. Originality/value: This paper has successfully validated an e-learning quality assurance questionnaire, which can be used effectively for evaluating e-learning programmes.